Os efeitos da aplicação dos princípios da teoria das restrições sobre a eficiência de uma cadeia de suprimentos de uma empresa do segmento químico - Barbosa, Luziane Machado (Universidade do Vale do Rio dos Sinos, 2023)
Solving the problems faced by Supply Chains (SCs) is a challenge for both academia and organizations. A promising alternative for solving these problems and improving the operational performance of SCs is the use of the Theory of Constraints (TOC). There is a lack of studies that seek to measure the efficiency of SCs. Based on the identification of this gap, this study aims to propose an approach that allows the aggregate measurement of these indicators, providing a complete and integrated view of the benefits arising from the adoption of TOC in CS in a chemical company. For this, Modeling was used as a research method. Efficiency was evaluated using Data Envelopment Analysis (DEA). The results revealed that the simultaneous implementation of the five TOC principles, and the use of demand forecasting, resulted in a significant increase in Supply Chain efficiency. Before applying TOC principles, the median efficiencies were 64%; after implementation, this median increased to 82%. The findings of this study provide evidence that the partial or isolated implementation of Theory of Constraints (TOC) principles in the Supply Chain, together with the omission of consideration of demand forecasting, can promote a significant reduction in efficiency.
Keywords: Teoria das Restrições; Cadeia de suprimentos; Eficiência da cadeia de suprimentos; Análise envoltória de dados; Theory of constraints; Supply chain; Supply chain efficiency; Data envelopment analysis; ACCNPQ::Engenharias::Engenharia de Produção